ADDRESSING TO CONSULTATIVE DIAGNOSTIC CENTER FOR CHARGEABLE MEDICAL AID - T.A. Gavrilova; G.A. Karkashadze; L.S. Namazova ("Paediatrician" Publishers LLC, 2007)
The flow formation of the applications to the state medical institutions for the paid medical care for the children is mostly chaotic. To reveal the sources of application for the paid medical care, the researchers carried on the questionnaire based survey, whose findings are given in the article. The authors defined the main application areas for the obtained information to be used by the government structures, while regulating the processes of application for the paid medical care.Key words: children, paid medical care.